Micro Spectrophotometric Determination and Cloud Point Extraction of Sulphadimidine Sodium in Pure form and Pharmaceutical Drug - Dhahir et al. (مجلة بغداد للعلوم)
Two simple, rapid, and useful spectrophotometric methods were suggest or the determination of sulphadimidine sodium (SDMS) with and without using cloud point extraction technique in pure form and pharmaceutical preparation. The first  method was based on  diazotization of the Sulphdimidine Sodium drug by sodium nitrite at 5 ºC, followed by coupling with α –Naphthol in basic medium to form an orange colored product . The product was stabilized and its absorption was measured at 473 nm. Beer’s law was obeyed in the concentration range of (1-12) μg∙ml-1. Sandell’s sensitivity was 0.03012 μg∙cm-1, the detection limit was 0.0277 μg∙ml-1, and the limit of Quantitation was 0.03605μg∙ml-1.The second method was the cloud point extraction (CPE) using Trtion X-114 as surfactant. Beer’s law was obeyed in the concentration range of (1-12) μg∙ml-1. Sandell’s sensitivity was 0.02958 μg∙cm-1, the detection limit was 0.01745 μg∙ml-1, and the limit of quantitation was 0.028303 μg∙ml-1. All variables including the reagent concentration, reaction time, color stability period, and mole ratio were studied in order to optimize the reaction conditions. The mole ratio for the composition of product is (1:1). Both methods were effectively useful to the determination of sulphdimidine sodium in pharmaceutical dose form.  The attained results were in a good agreement with the official and other methods in the literature .No interference were observed from the commonly encountered additives and excipients.